Vitamin D regulates transepithelial acid secretion in zebrafish (Danio rerio) larvae - Lin, Chia-Hao; Liu, Sian-Tai; Wang, Yu-Chun; Tsou, Yi-Ling; Hu, Huei-Jyun (Frontiers in Marine Science, 2022)
Maintenance of an acid-base balance is essential for normal physiological processes in vertebrates. Freshwater fishes live in an aquatic environment with variable pH, and their buffering capacity for acid-base balance in body fluids is weak. Thus, after acid exposure, fishes secrete excess acid to prevent internal acidosis. Acid-secreting ionocytes present in the adult gills and embryonic skin are primarily responsible for acid secretion, and H+-ATPase and Na+/H+ exchanger 3 (NHE3) are the two main transporters responsible for apical acid secretion. Vitamin D is a well-known hormone involved in the maintenance of Ca2+ homeostasis and is suggested to be involved in acid-base regulation by modulating the activity and/or mRNA expression of NHE3 in mammalian models. It remains unclear whether vitamin D is involved in acid secretion in fishes. The aim of the present study was to use zebrafish as a model to determine whether vitamin D and its receptors influence acid secretion. Our results indicated that the levels of 1α, 25-dihydroxyvitamin D3 (1α,25(OH)2D3), the bioactive vitamin D, were significantly increased in 3 days post-fertilization zebrafish larvae after exposure to acidic freshwater (AFW, pH 4.0). Exogenous 1α,25(OH)2D3 (20 μg/L) incubation substantially enhanced the mRNA expression of acid-secreting transporters and acid secretion at the skin of the entire body and each H+-ATPase-rich cell (HRC), a type of acid-secreting ionocyte. Furthermore, the expression of vitamin D receptors (VDRs) was identified in HRCs of zebrafish. When both VDRa and VDRb were knocked down, acid secretion and the mRNA expression of acid-secreting transporters were significantly decreased. Moreover, double knockdown of VDRa/b prevented the increase in acid secretion induced by AFW and 1α,25(OH)2D3 treatment. This study is the first to indicate that vitamin D is involved in acid secretion in fish.